Adenyl cyclases and cAMP in plant signaling - past and present - Gehring, Chris (BioMed Central, 2010)
In lower eukaryotes and animals 3'-5'-cyclic adenosine monophosphate (cAMP) and adenyl cyclases (ACs), enzymes that catalyse the formation of cAMP from ATP, have long been established as key components and second messengers in many signaling pathways. In contrast, in plants, both the presence and biological role of cAMP have been a matter of ongoing debate and some controversy. Here we shall focus firstly on the discovery of cellular cAMP in plants and evidence for a role of this second messenger in plant signal transduction. Secondly, we shall review current evidence of plant ACs, analyse aspects of their domain organisations and the biological roles of candidate molecules. In addition, we shall assess different approaches based on search motifs consisting of functionally assigned amino acids in the catalytic centre of annotated and/or experimentally tested nucleotide cyclases that can contribute to the identification of novel candidate molecules with AC activity such as F-box and TIR proteins.